Investigation on temperature characteristics of high voltage cable joints - Yong, Xu; Xin, Zhou; Ke, Zhu; Feiyue, Teng (Frontiers in Physics, 2025)
IntroductionExplosion-proof shells are essential for installing high-voltage cable joints in tunnels. However, improper internal filling and external air cooling systems can hinder effective heat dissipation, leading to elevated joint temperatures. Investigating the heat dissipation characteristics and optimal air cooling strategies for these joints is critical to enhancing current carrying capacity and mitigating safety risks.MethodsThis study establishes a high-fidelity model of 220 kV high-voltage cable joints to examine the impact of different fillers and filling ratios within explosion-proof shells on joint heat dissipation. Additionally, an external air cooling model under tunnel laying conditions was developed to evaluate the effectiveness of various air cooling methods in improving joint thermal performance.ResultsFilling the explosion-proof shell with epoxy resin increased the joint’s current carrying capacity by 1.78 times compared to air. The joint temperature exhibited a linear rise with an increasing proportion of air. Furthermore, optimal heat dissipation was achieved when the tunnel wind direction was perpendicular to the cable joint axis, with a 2 m/s wind speed enhancing current carrying capacity by 1.38 times.DiscussionThe findings highlight the importance of material selection and air cooling strategies in optimizing the thermal performance of high-voltage cable joints. This study provides theoretical insights for improving joint current carrying capacity and reducing main insulation temperature rise, offering practical guidance for engineering applications in tunnel environments.